ChatGPT from The Perspective of Surah Al-Imran: 19 Technology and Da’wah Media: A Case Study on Youtube - Khairunisa, Nabila (Proceedings of Annual Islamic Conference for Learning and Management, 2024)
ChatGPT (Chat Generative Pre-Trained Transformer) is an advanced learning tool designed to provide information across a wide range of topics, including science, culture, education, customs, and religious matters such as Islam. Developed by OpenAI in the United States, this tool offers significant benefits, but it also carries potential drawbacks. One of the noteworthy aspects of ChatGPT is its role in facilitating dialogue on philosophical and religious questions, including those posed by non-Muslims regarding Islam. This phenomenon can provide an opportunity for da’wah (Islamic outreach), particularly in educating those who may lack knowledge of the religion. The purpose of this research is to explore how ChatGPT is being used as a medium for da’wah, especially in the context of addressing questions from non-Muslims about Islam. This study adopts a qualitative research approach, gathering observational data from YouTube content related to these interactions. A key point in the discussion is derived from the Quran, specifically from Surah Al-Imran: 19 which states, "Indeed, the religion in the sight of Allah is Islam." This verse underscores the belief in Islam as the true and final religion in the eyes of Allah (SWT). The research calls for further in-depth examination of how Islamic teachings, as articulated in the Quran and Hadith, align with other verses and how they are presented in platforms like ChatGPT. By critically engaging with these sources, the aim is to foster a deeper understanding of Islam and its teachings in the face of modern technological challenges.